Membaca Ulang Etika Dakwah di Era Digital: Integrasi AI, Literasi Media, dan Argumentasi Keagamaan - Rohman Suhratun; Nabila al-Athiriyah (Journal of Da'wah, 2025)
Digital transformation has fundamentally reshaped the landscape of Islamic preaching, presenting complex ethical challenges amid the dominance of algorithms and artificial intelligence. This study employs a qualitative approach using a systematic literature review of 52 journal articles and 8 academic books published between 2015 and 2024. Thematic analysis identifies four critical dimensions: (1) the use of AI in automating religious content; (2) the ethical shift from moral responsibility toward popularity and monetization; (3) the low level of digital literacy among preachers and audiences in dealing with hoaxes and algorithmic manipulation; and (4) the extreme simplification of religious arguments that neglect contextual interpretation. Findings reveal that platform algorithms actively shape content and norms of preaching through systems privileging engagement over substantive depth. This study proposes an integrative model with five pillars: algorithm-aware ethics, digitally-informed scholarship, critical media literacy, contextual argumentation, and transparent practice. Practical implications include the need for digital literacy education, the development of alternative platforms grounded in Islamic values, and the transformation of Islamic education curricula to integrate critical understanding of digital technologies. Theoretical contribution lies in extending mediatization theory, enriching algorithmic ethics discourse, and deepening critical media literacy within the context of digital Islamic preaching, offering a novel interdisciplinary framework beyond previous studies.